(untitled) (Homoeopathy for All, 2021)
Anorectal disorders include a diverse group of pathologic disorders that generate significant patient discomfort and disability. Although these are frequently encountered in general medical practice, they often receive only casual attention and temporary relief, since most patients with symptoms referable to the Ano rectum do not seek medical attention.